ROLE OF METAPHORS IN ENGLISH LITERATURE - Rakhmonova Amira Ulfatovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract. This article explores the vital role of metaphors in English and American literature, tracing their evolution, functions, and enduring impact. From early works to contemporary pieces, metaphors enrich texts, offering layers of meaning and symbolism. Drawing from diverse influences, writers use metaphors to convey the complexities of the English, American experience and address social issues. As English and American literature evolves, metaphors remain essential, connecting past and present while illuminating the human condition.